Antibiotic resistance changes in strains of bacteria and yeast-like fungi following their growth in established cell lines of human and animal origin - Rybalko, S.L.; Pokas, Ye.V.v; Dieyev, V.A.; Liaskovski, T.M.; Furzikova, T.M.; Diadiun, T.M.; Diadiun, S.T.; Ivanskaya, N.V.; Nastoyashcha, N.I.; Verkhatsky, P.P.; Salkov, S.T. (Біополімери і клітина, 2006)
The phenomenon of the susceptibility and reversion of resistance to antibiotics in strains of bacteria and yeast-like molds has been identified upon the interaction of bacteria and molds with transplantable human and animal cell lines depending on the cultivation conditions. The ability of susceptibility reversion of bacteria and yeast-like fungi to some antibiotics is not stable, it varies with the passages. This phenomenon may be a reason of the poor efficacy of antibiotic treatment when the susceptibility of bacteria to antibiotics is assayed by the usual technique. The authors propose to modify the antibiotics-susceptibility assay currently used in clinics by co-culture of the isolated bacteria and fungi with the transplantable cell lines or human leukocytes. При взаємодії бактерій і грибів з клітинами людини та тварин ідентифіковано феномен реверсії чутливості та резистентності до антибіотиків бактерій і грибів. Властивість реверсії чутливості бактерій і грибів до деяких антибіотиків нестабільна, вона змінюється від пасажу до пасажу, що може обумовлювати неефективність лікування антибіотиками при чинних методах встановлення чутливості до антибіотиків бактерій і грибів. Автори пропонують модифікувати тест антибіотикочутливості бактерій і грибів, виділених на поживних середовищах, культивуванням їх у культурі перещеплюваних клітин або лейкоцитах людини. При взаимодействии бактерий и грибов с клетками человека и животных идентифицирован феномен реверсии чувствительности и резистентности к антибиотикам бактерий и грибов в зависимости от условий выращивания. Свойство реверсии чувствительности бактерий и грибов к некоторым антибиотикам нестабильно, оно изменяется от пассажа к пассажу, что может обусловливать неэффективность лечения антибиотиками при существующем методе определения чувствительности к антибиотикам бактерий и грибов. Авторы предлагают модифицировать тест антибиотико-чувствительности бактерий и грибов, выделенных на питательных средах, культивированием их в культуре перевиваемых клеток или лейкоцитах человека.